2020
DOI: 10.18388/abp.2020_5394
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments of MALDI MSI application in plant tissues analysis

Abstract: Mass spectrometry imaging (MSI) combined with matrix-assisted laser desorption/ionization (MALDI) is an efficient technology applied in plant metabolomics research. This technique allows for visualization of spatial distribution of metabolites such as: lipids, proteins, peptides and DNA sequences, by determining the x, y coordinates of the compounds exactly in plant tissue. Simplicity of the tissue preparation without the need of prior exact knowledge about the analytes is a great advantage of this method. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Besides, as shown in Figure 13, the resolution of recent nano laser probe-based MSI systems can be down to the nm level (subcellular level) by introducing desorption laser with a micro-lensed fiber, proving a great development in MALDI-MSI (Meng et al, 2020). Considering the lack of selectivity of samples of MALDI ionization (Susniak et al, 2020) and the ability to detect DNA (Kirpekar et al, 1999;Ehrich et al, 2005), we believe that MALDI will become more and more important in MSI.…”
Section: Future Directionsmentioning
confidence: 99%
“…Besides, as shown in Figure 13, the resolution of recent nano laser probe-based MSI systems can be down to the nm level (subcellular level) by introducing desorption laser with a micro-lensed fiber, proving a great development in MALDI-MSI (Meng et al, 2020). Considering the lack of selectivity of samples of MALDI ionization (Susniak et al, 2020) and the ability to detect DNA (Kirpekar et al, 1999;Ehrich et al, 2005), we believe that MALDI will become more and more important in MSI.…”
Section: Future Directionsmentioning
confidence: 99%
“…Advancements in MALDI IMS instrumentation for improved resolution and sensitivity, sample preparation workflows including innovative chemical strategies for on-tissue chemical derivatization or to generate novel matrices, and data management and processing, offer the ability to precisely quantify tissues molecular abundances with a high-resolution level [25][26][27][28][29]. MALDI IMS technology is now used for analyses of biological samples belonging to both plant (for reviews see [30][31][32][33]) and animal kingdoms including human specimens [23,34,35]. Given the increasing use of MALDI IMS on animal models, this approach was also investigated on different invertebrate models and for the first time in insects to map neuropeptides within the neuronal tissues of the cricket Acheta domesticus [36].…”
Section: Biomarkers Like Lipidsmentioning
confidence: 99%
“…A spectral image of each ion detected can be created. 11 In 2009, Holscher et al reported, by laser desorption/ ionization (LDI) MSI analysis, the spatial distribution of hypericins, secondary metabolites of intact leaves, and flowers of Hypericum perforatum and H. reflexumsem. The use of a matrix was unnecessary, since these compounds already have high-energy absorption at the focused laser wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…14 MALDI MSI enables the visualization of the spatial distribution of several metabolites in the plant tissue. 11 Identifying the chemical profile of a plant species is essential in the search for plant metabolites with potential cosmetic applications, such as phenolics, polyphenols, flavonoids, terpenoids, polysaccharides, and organic acids. 15 Several plants that are popularly used due to their benefits for the skin 16 end up being tested for cosmetic purposes.…”
Section: Introductionmentioning
confidence: 99%